The Welfare State and Liberal Democracy: A Political Economy Approach - Heise, Arne; Khan, Ayesha Serfraz (World Review of Political Economy, 2019)
This article attempts to shed some light on the developments of welfare states in highly developed nations since World War Two (WW2) within the context of a narrative which seeks to combine institutional distinctions, termed “varieties of capitalism,” with the historical regimes of regulation theory in a political economy perspective which puts interested political actors at center stage. It will be argued that in a liberal democracy, the elite has the framing and agenda-setting power to “manufacture a political will” according to its interests. The welfare state is not the result of a long social struggle on the part of the needy; rather, it results in its general features from the minimal state of meritocratic exigencies. Under the very peculiar circumstances of the post-WW2 era, this even translated into a rise in social welfare spending to more than a third of national income. The particular design of welfare state organization was the subject-matter of political conflict, and a clear distinction between liberal and coordinated market economies can be attributed to cultural differences and institutional settings. Yet the core of the welfare state conception serves the interest of the meritocracy as much as those who benefit from social programs and redistribution. And the neoliberal attack on the welfare state since the 1980s is not a necessary re-calibration due to changing economic conditions or a growing lack of solidarity among the people but an expression of a modified cost–benefit analysis from the elite's perspective.